Gender Perspective of Interpersonal Relationships in Pre-Tertiary Schools as a Teacher Motivator - Thomas N. Tindan; Moses A. Abubakari; Victor Antwi; Philip Dorsah; Dennis Offei Kwakye (Richtmann Publishing, 2023)
Teachers are motivated by a variety of variables while they carry out their employment. However, the expected impact on teacher motivation has not been achieved as a result of the economic reasons. Numerous studies have demonstrated that social elements, such as satisfying interpersonal interactions, can spur people to pursue and accomplish a goal. But there has been a lot of silence over how this varies by gender. This made it necessary to conduct research to determine how interpersonal interactions (IR), specifically those between teachers and students, teachers and other teachers, and teachers and heads of schools in Ghana's Upper East Region (UER), affected teachers' motivation. A cross-sectional survey study design was used, and the data collection process used a mixed technique approach. Teachers at pre-tertiary institutions in UER in Ghana are the target demographic. 831 female and 1,719 male instructors from the area made up the sample. The data was gathered using a teacher motivation scale comprising 4 Likert scale questions and an interview schedule for focus group discussions. The findings demonstrated that interpersonal interactions at school (TP, TT, and TH) influence how instructors in pre-tertiary institutions in Ghana's Upper East Region (UER) carry out their duties, with TT offering the greatest incentive and TH the least. Although IR generally has no association with gender, Pearson's chi-square study revealed that TT as a teacher motivator is associated to gender. To encourage male and female teachers to fulfil their jobs, it is important to foster positive interpersonal interactions at pre-tertiary institutions. Being able to establish close relationships with one's co-workers is key to enjoying one's job as a teacher. Therefore, it is crucial that educators work hard to cultivate good relationships with their colleagues. Received: 12 August 2022 / Accepted: 29 December 2022 / Published: 5 January 2023